Qualitative assessment of Listeria monocytogenes exposure among consumers of milk in informal markets in Ghana - Tano-Debrah, K.; Appiah, J.; Annor, G.A.; Alpha, M.M.; Makita, K.; Grace, Delia (2011)
BACKGROUND: Raw, unpasteurized milk is regularly consumed in some communities in Ghana, especially among the Fulani ethnic group. However, unpasteurized raw milk has been implicated in outbreaks of food borne diseases, including listeriosis, in many countries. The production and consumption of milk has become an informal cottage industry in Ghana. Recent years have also seen increasing reports of human illness compatible with listeriosis. This study was conducted to investigate the risk of consuming raw milk and its products that may be contaminated with Listeria monocytogenes, the pathogen that causes listeriosis, in Ghana. This was the first study on the risk of exposure to listeriosis from raw milk in Ghana. METHODS: A survey was carried out in selected raw milk consuming communities to assess the potential prevalence of listeriosis and to establish the raw milk pathways and milk production and handling practices. Participatory appraisals were conducted with retailers and the milk value chain mapped. A fault tree was developed and exposure assessment was then qualitatively assessed. Based on this critical control points were identified. RESULTS: Results showed health indicators suggestive of listeriosis in the study area, such as high prevalence of spontaneous abortion, meningitis and diarrhoea in people. Participatory appraisal showed multiple stakeholders whose activities could contribute to the risk of microbial infection, including listeriosis. The important stakeholders are the farmers who do the milking, the assemblers, and the retailers. Value chain mapping found milk from urban, periurban and milkshed producers all flowed to assemblers and from thence by a variety of paths to consumers. The fault-tree generated suggested that infection with L. monocytogenes could result from consuming unpasteurized raw milk contaminated through sources such as cattle, serving and transport utensils, as well as cross-contamination during handling. The results suggest that the highest level of exposure is associated with milk consumed in the retail market and identified the handling practices that might lead to this. (This result was confirmed by a quantitative analysis). Exposure to the pathogen was higher from fermented unpasteurized raw milk retailed on the informal market than boiled raw milk. Boiling could be used to reduce the occurrence of the pathogen in the raw milk samples. SUMMARY: Listeriosis is much under-researched in Africa and this study represents one of the first attempts to understand its importance in Ghana. This study combining health surveys, participatory appraisals, value chain mapping and qualitative risk assessment increased understanding of the risk of listeriosis and suggested critical control points where risk could be mitigated.